EFEKTIVITAS IMPLEMENTASI VISA ON ARRIVAL (VOA) TERHADAP PEMBANGUNAN DAERAH DI BALI DARI SEKTOR PARIWISATA - Agus Surya Manika; Ni Nengah Agustin Citrawati; Ni Made Rai Sukardi (Jurnal Ilmiah Raad Kertha, 2025)
Bali is an area where one of the largest incomes comes from the tourismindustry. Tourism plays an important role in sustainable development in Bali. Sincebeing hit by the Covid 19 pandemic, development in Bali has been hampered. Torestore Bali's economy in the tourism sector, the government has created a strategywith a Visa on Arrival (VoA) policy for foreign tourists from several countries. Thisresearch was conducted to find out the effectiveness of the implementation of Visa onArrival (VoA) on regional development in Bali from the tourism sector and the impactresulting from the implementation of Visa on Arrival (VoA) in Bali. This research usesa normative method, using a case approach. Based on research, it was found that thesurge in tourist visits as a result of the implementation of the VoA policy gave rise tovarious new problems for the tourism industry in Bali, so the effectiveness of this policyneeds to be reviewed comprehensively and the negative impact of the implementationof VoA has resulted in mass tourism which has an impact on the sustainability oftourism objects in Bali.